A taxonomic study of three mealybug species (Hemiptera: Coccomorpha: Pseudococcidae) infesting dwarf bamboo in Japan, with description of a new species - Tanaka, Hirotaka (Zootaxa, 2022)
The taxonomic status of some mealybug species (Hemiptera: Coccomorpha: Pseudococcidae) found on dwarf bamboos in Japan are reviewed. A species currently placed as a junior synonym of Paraputo angustus (Ezzat & McConnell 1956) was found to differ from P. angustus by having dorsal oral collar tubular ducts of two sizes rather than one, so it is revived as Formicococcus bambusiphilus (Takahashi 1958) stat. rev. and comb. nov.; it is redescribed, based on the lectotype and a paralectotype designated in this study and additional adult females collected more recently. A new species, Formicococcus kawaii sp. nov., is described; it is similar to F. bambusiphilus and Paraputo angustus (Ezzat & McConnell 1956) but differs from them in having 18 pairs of cerarii, relatively large antennae and hind legs, and a dumbbell-shaped circulus. The characterization of a third dwarf bamboo-feeding species, Paraputo kaiensis (Kanda 1932), is updated based on adult females collected by the original describer and material collected more recently. Paraputo kaiensis resembles P. pauper (Danzig 1971) but differs in lacking translucent pores on the hind legs and in possessing a circulus. It also differs from most species of Paraputo Laing by having the anal opening situated on the posterior margin of the dorsum and an elongate-oval body, so the generic placement of this species remains questionable. Identification keys to separate mealybug genera with anal lobe bars and without oral rim ducts found in Asia, and to species of adult female Formicococcus in Japan and Paraputo in East Asia are provided.